2021
DOI: 10.1093/cid/ciab003
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism and Major Bleeding in Patients With Coronavirus Disease 2019 (COVID-19): A Nationwide, Population-Based Cohort Study

Abstract: Background Venous thromboembolism (VTE) is a potentially fatal complication of SARS-CoV-2 infection and thromboprophylaxis should be balanced against risk of bleeding. This study aimed to examine risks of VTE and major bleeding in hospitalized and community-managed SARS-CoV-2 patients compared with control populations. Methods Using nationwide population-based registries, 30-day risks of VTE and major bleeding in SARS-CoV-2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 42 publications
6
54
2
3
Order By: Relevance
“…Our event rates were, however, standardised for any differences in sex and age, and use of systemic hormone therapy was not higher in our vaccine recipients than in the general population, and surgery or immobilisation is unlikely to be increased in members of the active work force. Similarly, as also observed in our post hoc analyses, any increase in observed venous thromboembolic events was unlikely to be explained by SARS-CoV-2 infections occurring in vaccinated people, as both the prevalence of covid-19 and the associated absolute risk of thromboembolic events was low in our setting 32. Our post hoc confounder analysis (E-values) suggested that our findings were unlikely to be explained by unmeasured confounders.…”
Section: Discussionsupporting
confidence: 87%
“…Our event rates were, however, standardised for any differences in sex and age, and use of systemic hormone therapy was not higher in our vaccine recipients than in the general population, and surgery or immobilisation is unlikely to be increased in members of the active work force. Similarly, as also observed in our post hoc analyses, any increase in observed venous thromboembolic events was unlikely to be explained by SARS-CoV-2 infections occurring in vaccinated people, as both the prevalence of covid-19 and the associated absolute risk of thromboembolic events was low in our setting 32. Our post hoc confounder analysis (E-values) suggested that our findings were unlikely to be explained by unmeasured confounders.…”
Section: Discussionsupporting
confidence: 87%
“…A high frequency of blood clots has been observed in CoViD-19 [ 36 ]. Despite healthcare organizations did not alert about an increased risk of thrombohemorrhagic events following the BNT vaccine, the hypothesis that the SARS-CoV-2 spike protein produced following vaccine administration favors blood clots cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In a recent nationwide Danish study, the incidence of VTE in patients hospitalized with COVID-19 was reported at 4% in patients admitted to the wards and 11% in patients admitted to the ICU. 5 …”
Section: Discussionmentioning
confidence: 99%